การคาดประมาณอัตรามรณะไทย : การเปรียบเทียบ 3 วิธีการ (ลี-คาร์เตอร์ ฟัซซีลี-คาร์เตอร์ และการแปลงของแวง) - ณัฐกร สุรเมธากุล (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
This research aims to forecast the mortality rate of the Thai population in the next 10 years by using 3 projection methods: 1) The Lee-Carter Model, 2) Fuzzy Formulation of the Lee Carter Model, and 3) Wang Transform. In addition to comparing the estimates from 3 methods using mean absolute percent error (MAPE). Data used in the study are the number of population and the number of death by age and sex of the year 1998-2008 from the Ministry of Interior and the Ministry of Public Health respectively. The results showed that the Lee-Carter model is a model with the lowest average MAPE for both male and female. However if considering each age group, the Wang transform method gives the most minimum MAPE in male and the Lee-Carter model provides the most minimum MAPE in female. Moreover, it also found that the projections of the mortality rates over the next 10 years from 3 methods are in the same feature and slowly decreasing. For 1 year of age and 20-40 years of age, mortality rates have decreased slightly faster than other age